(untitled) (Journal of the College of Basic Education, 2025)
Today’s computer science teaching methods are among those that still rely on the traditional aspects of their curricula, employed by teachers in most schools, in developing countries in general, and in Iraq in particular. These methods lack a modern, practical or applied aspect, and therefore do not encourage the development of diverse types of thinking among students. These calls for teachers to adopt modern teaching methods, strategies, and models that can help them overcome and overcome the difficulties facing learners in teaching computer science. Reciprocal teaching is a multi-component approach that combines four strategies into a single, cohesive structure to enhance text comprehension: prediction, clarification, questioning, and summarization. This approach helps teachers clearly promote learning, helping students become more aware of their reading and learning. "To identify the impact of the reciprocal teaching method on raising the academic achievement of fifth-grade female students in computer science." To verify the research objective, the researcher formulated the following hypotheses: There is no statistically significant difference at the (0.05) level between the average scores of the experimental group taught using the reciprocal teaching method and the average scores of the control groups taught using the traditional method in raising their academic achievement in the computer subject in the post-test. There is no statistically significant difference at the (0.05) level between the average scores of the experimental group taught using the reciprocal teaching method and the average scores of the control groups taught using the traditional method in the Predicting skill in the post-test. There is no statistically significant difference at the (0.05) level between the average scores of the experimental group taught using the reciprocal teaching method and the average scores of the control groups taught using the traditional method in the summarization skill in the post-test. There is no statistically significant difference at the (0.05) level between the average scores of the experimental group taught using the reciprocal teaching method and the average scores of the control groups taught using the traditional method in the Questioning skill in the post-test. In order for the researcher to reach the research results, she built a test for the computer subject for fifth-grade female students consisting of (15) questions, divided into three areas, which are (prediction, summary, questioning), and each area consists of (5) objective questions of the multiple-choice type. She applied the test to (200) female students in order to extract its psychometric properties, and then she withdrew the female students who obtained scores less than the hypothetical average of (7.5), after which she divided the female students into two groups (experimental and control), each group consisting of (20) female students, and then she carried out the equivalence operations between the two groups, and after applying her experiment using the reciprocal teaching method, the results of the post-test showed the following: 1-The program using the reciprocal teaching method has an impact on raising academic achievement in computer science. 2-The program using the reciprocal teaching method has an impact on raising academic achievement in computer science by developing prediction skills. 3-The program using the reciprocal teaching method has an impact on raising academic achievement in computer science by developing summarization skills. The program using the reciprocal teaching method has an impact on raising academic achievement in computer science by developing questioning skills.